The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1080/00039896.1988.9935860
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Actual and Perceived Residential Proximity to Toxic Waste Sites

Abstract: Studies of Memphis and Three Mile Island have noted a positive association between actual residential distance and public concern about exposure to the potential of contamination, whereas none was found at Love Canal. In this study, concern about environmental contamination and exposure was examined in relation to both perceived and actual proximity to a toxic waste disposal site (TWDS). It was hypothesized that perceived residential proximity would better predict concern levels that would actual residential d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…employment (Wiegman et al, 1991), as well as psychological mechanisms, such as cognitive dissonance-reducing heuristics, which increase risk acceptance in long-term residents in contaminated areas (Grasmück and Scholz, 2005). Interestingly, Howe (1988) found that perceived (self-reported) distance from chemical disposal sites was strongly associated with the level of concern expressed by residents, while actual distance was not. Our findings also support that reported traffic intensity is a better predictor of risk perception than living close to major roads.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…employment (Wiegman et al, 1991), as well as psychological mechanisms, such as cognitive dissonance-reducing heuristics, which increase risk acceptance in long-term residents in contaminated areas (Grasmück and Scholz, 2005). Interestingly, Howe (1988) found that perceived (self-reported) distance from chemical disposal sites was strongly associated with the level of concern expressed by residents, while actual distance was not. Our findings also support that reported traffic intensity is a better predictor of risk perception than living close to major roads.…”
Section: Discussionmentioning
confidence: 91%
“…Research on the perception of risk in relation to pollution has produced conflicting results (Howe, 1988;Grasmück and Scholz, 2005;Moffatt et al, 2000;Poortinga et al, 2008). Concern about specific environmental threats is likely to be a local phenomenon, depending on local benefits associated with industrial facilities, e.g.…”
Section: Discussionmentioning
confidence: 96%
“…Perception of closeness to potential contamination sources was a significant predictor of concern in this study. A study comparing the actual distance and perceived proximity to inactive toxic waste disposal sites is reported in another paper where actual distance was not related to concern level, while perceived proximity was significantly related (14).…”
Section: Discussionmentioning
confidence: 99%
“…This concept of chemical time bombs has emerged in the past few decades through environmental toxicology investigations and results of environmental remediation. Our perceptions of the risk associated with exposures to toxic substances has likewise evolved (Howe, 1988).…”
Section: Alteration Of the Land And Time Scales Of Recoverymentioning
confidence: 99%